2014
DOI: 10.2139/ssrn.2487754
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Weather Events and Child Height: Evidence from Mongolia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…One study found that individuals who were of school age and living in severely affected districts during extreme weather shocks were significantly less likely to have completed mandatory education, compared to peers in less affected districts [40]. Another study conducted on the temperatures in school classrooms suggested that increased temperatures and poor air quality/ventilation cause headaches and poor academic performance [41].…”
Section: Educationmentioning
confidence: 99%
“…One study found that individuals who were of school age and living in severely affected districts during extreme weather shocks were significantly less likely to have completed mandatory education, compared to peers in less affected districts [40]. Another study conducted on the temperatures in school classrooms suggested that increased temperatures and poor air quality/ventilation cause headaches and poor academic performance [41].…”
Section: Educationmentioning
confidence: 99%